Mediation role of body fat distribution (FD) on the relationship between CAV1 rs3807992 polymorphism and metabolic syndrome in overweight and obese women - Faezeh Abaj; Said Abdul Ghafour Saeedy; Khadijeh Mirzaei (BMC, 2021)
Abstract Background Metabolic syndrome (MetS) is associated with an increased risk of morbidity and mortality in almost all chronic diseases. The most frequent methods for the calculation of a continuous MetS (cMetS) score have used the standardized residuals in linear regression (z-score). Recently, emerging data suggest that one of the main genetic targets is the CAV1, which plays a crucial role in regulating body fat distribution. This study is designed to investigate the relationship between CAV1 rs3807992 genotypes and cMetS, and to determine whether body fat distribution plays a mediating role in this regard. Methods The current cross-sectional study was conducted on 386 overweight and obese females. The CAV1 rs3807992 and body composition were measured by the PCR-RFLP method and bioelectrical impedance analysis, respectively. Serum profile of HDL-C, TGs, FPG, and Insulin were measured by standard protocols. Results GG allele carriers had significantly lowered Z-MAP (p = 0.02), total cMetS (p = 0.03) and higher Z-HDL (p = 0.001) compared with (A) allele carriers. There was a significant specific indirect effect (standardized coefficient = 0.19; 95% CI 0.01-0.4) of Visceral fat level (VFL). Although, total body fat was significantly associated with CAV1 rs3807992 and cMetS, the specific indirect effect was not significant (standardized coefficient = 0.21; 95% CI − 0.006, 0.44). VFL contributed to significant indirect effects of 35% on the relationship between CAV1 and cMetS. Conclusion Higher visceral adipose tissue may affect the relationship between CAV1 and cMetS. Although CAV1 rs3807992 is linked to VFL in our study, the influence of this polymorphism on MetS is not via total fat.